Joint effects of genes underlying a temperature specialization tradeoff in yeast - Alzaben, Faisal; Chuong, Julie N; Abrams, Melanie B; Brem, Rachel B (bioRxiv, 2021)
Abstract A central goal of evolutionary genetics is to understand, at the molecular level, how organisms adapt to their environments. Landmark work has characterized steric clashes between variants arising in a given protein as it evolves a new function. For many traits, any such single gene represents only part of a complex architecture, whose genetic mechanisms remain poorly understood. We studied the joint effect of eight genes underlying thermotolerance in Saccharomyces cerevisiae, when introduced into a thermosensitive species, S. paradoxus. The data revealed no sign epistasis: most gene combinations boosted thermotolerance, and none was deleterious. And the genes also governed a heretofore unknown advantage in cold growth by S. paradoxus. These results shed light on how and why thermotolerance arose in S. cerevisiae, and they suggest a paradigm in which, if protein repacking is a difficult step in adaptation, combining whole-gene modules may be far less constrained. Author summary The building of new traits by evolution can be difficult and slow. A given DNA variant may be the linchpin of a beneficial trait in some individuals and, in others, have the opposite effect—torpedo fitness altogether. Such effects have been best studied among amino acids in a given protein, whose changing side chains crowd each other unless they arise in a particular order. We set out to complement this literature by studying adaptive variants that are not in the same protein, but rather scattered across unlinked genes. We used as a model system eight genes that govern the ability of the unicellular yeast Saccharomyces cerevisiae to grow at high temperature. We introduced this suite of genes stepwise into a non-thermotolerant sister species, and found that the more S. cerevisiae loci we added, the better the phenotype. We saw no evidence for toxic interactions between the variant genes as they were combined. We also used the eight-fold transgenic to dissect the mechanism and the evolutionary forces underlying the thermotolerance trait. Together, our data suggest a principle for the field in which repacking a given protein is the hard part of evolution, and assembling combinations of unlinked loci is far easier. Competing Interest Statement The authors have declared no competing interest.